Family Refusal of Chemotherapy for Pediatric Cancer Patients. Issue 5 (July 2015) - Nassin, Michele L.; Mueller, Emily L.; Ginder, Curt; Kent, Paul M.
<x xml:space="preserve">Abstract</x> Background: Refusal of therapy is ethically acceptable for competent adults. Practitioner opinions regarding refusal of therapy in pediatric cancer patients has not been widely studied. This is the largest survey of oncology practitioners assessing support for refusal of chemotherapy. Procedure: Pediatric oncology nurses/physicians were asked: "As their provider I would support refusal of chemotherapy by a family, " with the following options: "Never support refusal, " "Always support refusal, " or "Support for refusal would depend on cure rate, age, or both." Variables assessed were: age (0 to 7, 8 to 13, 14 to 17 y) and cure rate (0% to 33%, 34% to 66%, 67% to 100%). Results: A total of 957 practitioners responded. Fifty-six percent, 31%, and 0.2%, respectively, stated their support of chemotherapy refusal depended on "age and cure rate, " "cure rate alone, " or "age alone." Two percent and 11% indicated they would "always" or "never" support refusal, respectively. For a "modest" or "good" cure rate, support for refusal was <20%, whereas for a "poor" cure rate, the majority would support a family's refusal (53% to 78% age dependent). Within each cure rate, respondents were more likely to support refusal for older patients (P<0.001). Conclusions: The majority of practitioners surveyed viewed parental refusal of chemotherapy for children with a moderate or good expected cure rate as unacceptable, but were more accepting of refusal with a poor prognosis, especially for teenagers.